Time of aggregate destruction as a parameter of soil water stability within an agricultural hummocky moraine landscape in northern Poland - Hanna Radziuk; Świtoniak, Marcin (Bulletin of Geography. Physical Geography Series, 2022)
Slaking is a rapid wetting of soil aggregates that affects their stability in the face of the effects of water. The aggregate’s stability has an indirect influence on soil functioning through its minimising of soil erosion. Testing slaking is very simple, does not need additional complicated equipment and could be done for any point. Testing was performed for natural air-dry aggregates (7–10 mm) sampled from the arable layers of four different types of soils within a young hummocky moraine landscape: Eutric Regosol (Protocalcic), Haplic Luvisol (Protocalcic), Albic Luvisol, Mollic Gleysol. The soil tests were performed on a soil-erosive catena located in Chełmno Lake District (Northern Poland) from the tops of hummocks and from the shoulder to bottom part of depressions. The test results demonstrated a significant decrease in aggregate stability from Mollic Gleysol to Eutric Regosols (Protocalcic) – that is, from colluvial soils at depressions to completely eroded hummock-top soils. However, 75% of all aggregates in Eutric Regosols were unstable when time of aggregate destruction was less than 300 sec. Oppositely to Eutric Regosols laying on hummock tops, 70% of aggregates of Mollic Gleysols in depressions were water stable. The mean time for aggregate destruction for each soil from hummock-top to depression was 209 sec. for Eutric Regosol, 375 sec. for Haplic Luvisol, 616 sec. for Albic Luvisol and 772 sec. for Mollic Gleysol. The main soil properties that affected the time of aggregate destruction are clay content (very strong negative correlation; r=–0.72); soil organic carbon content (strong positive correlation; r=0.69), and content of secondary carbonates (strong negative correlation; r=–0.69).